The Impact of Invasive Exotic Grasses on Quail in the Southwestern United States - William P. Kuvlesky Jr.; Timothy E. Fulbright; Ron Engel-Wilson (National Quail Symposium Proceedings, 2017)
Five native quail species inhabit arid and semi-arid ecosystems in the southwestern United States. One species is endangered, one species is declining throughout it’s historic range, another species is declining in portions of its historic range, and the other two species may be beginning to decline in selected portions of their respective ranges. A number of factors have been implicated for these declines, though habitat loss is frequently cited as the most common factor associated with southwestern quail declines. Exotic species invasions in the United States represent a significant economic and biological threat to the United States. Many exotic organisms introduced to the United States are threatening entire ecosystems, replacing native species and even threatening other native species with extinction. Numerous exotic grasses are invading arid and semi-arid ecosystems in the Southwest. Most exotic grasses were intentionally introduced for erosion control and to provide forage for livestock. Cattlemen sometimes favor exotic grasses in spite of their impacts to native biodiversty. The impacts of exotic grasses on vegetative communities are discussed, as well as their potential impacts on the five native quail species that inhabit the southwestern United States. Exotic grass eradication and control are also discussed, as well as introducing exotic grass pest management into existing land management programs. Research designed to determine the impacts of exotic grass invasions on quail and their habitat is recommended.
Keywords: Callipepla gambelii; C. squamata; Colinus virginianus; C. v. ridgwayi; Cyrtonyx montezumae; eradication; exotic grass; forb; Gambel’s quail habitat; insect; management; Masked bobwhite; Montezuma quail; native vegetation; northern bobwhite; research; scaled quail; southwest